Bimbingan Teknis Tata Kelola Keuangan dan Anggaran Berbasis Kinerja Sekolah Tinggi Ilmu Kesehatan (Stikes) Muhammadiyah Palembang - Zulfikar Zulfikar; Rosida Nur Syamsiyati; Ahmad Muttaqin (Universitas Mathla'ul Anwar Banten, 2019)
TECHNICAL ASSISTANCE FINANCIAL REPORTING AND BUDGETING BASED PERFORMANCE IN STIKES MUHAMMADIYAH PALEMBANG. The purpose of this technical assistance activity were to provide knowledge and insights related to the financial management and performance based budgeting to the principal and budget user of STIKES Muhammadiyah Palembang and to help compile the work program. This activity was attended by 23 leaders from various levels.Materials that provided were, performance based budgeting, best practices, and financial reporting. The results of technical assistance for performance based budgeting indicate an increase in the ability of participants to develop budgets. Evaluation of the participants showed that they were very enthusiastic about following the activity from beginning to end.